2022
DOI: 10.51535/tell.1148725
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Teachers’ Classroom Management Anxiety: The Role of Educational Technology Usage in Classrooms

Abstract: The current study reveals whether there is a significant relationship between the level of teachers' use of educational technologies and classroom management anxiety. In the study, Levels of Educational Technology Usage scale and Classroom Management Anxiety scale were used as data collection tools. In the results of the research, it was determined that there was a significantly weak and negative relationship between the level of teachers' use of educational technologies and their classroom management concerns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…When the literature on this subject is examined, it is seen that the results obtained in the study exhibit similarities and differences between the results obtained in the study and other studies. Kayhan (2022) found that the level of educational technology use of male teachers was higher than that of female teachers. Cebi and Reisoglu (2020) determined in their study that there were significant differences in favor of male pre-service teachers in the sub-dimensions of information and data literacy, digital content production, security, and problem-solving.…”
Section: Discussionmentioning
confidence: 94%
“…When the literature on this subject is examined, it is seen that the results obtained in the study exhibit similarities and differences between the results obtained in the study and other studies. Kayhan (2022) found that the level of educational technology use of male teachers was higher than that of female teachers. Cebi and Reisoglu (2020) determined in their study that there were significant differences in favor of male pre-service teachers in the sub-dimensions of information and data literacy, digital content production, security, and problem-solving.…”
Section: Discussionmentioning
confidence: 94%
“…Keskin (2019) similarly categorizes them in five groups: institutional problems (teaching hours, classroom environment, and class size); instructional problems (curriculum, materials, teaching techniques, and first language use); learner-related problems peculiar to YLs' characteristics (attention, motivation, anxiety, and development); teacher-related challenges (proficiency, classroom management, and ineffective body language); and community-related problems (parents' roles in the learning process and different first languages). Kayhan (2022) also argues that classroom management is probably one of the most challenging aspects of teaching YLs, and it has the potential to cause anxiety among teachers. Relatedly, TEYL requires teachers to adapt their teaching techniques, review YLs' pedagogical characteristics or needs, and subsequently rearrange the classroom environment.…”
Section: Challenges Of Teylmentioning
confidence: 99%
“…Keskin (2019) similarly categorizes them in five groups: institutional problems (teaching hours, classroom environment, and class size); instructional problems (curriculum, materials, teaching techniques, and first language use); learner-related problems peculiar to YLs' characteristics (attention, motivation, anxiety, and development); teacher-related challenges (proficiency, classroom management, and ineffective body language); and community-related problems (parents' roles in the learning process and different first languages). Kayhan (2022) also argues that classroom management is probably one of the most challenging aspects of teaching YLs, and it has the potential to cause anxiety among teachers. Relatedly, TEYL requires teachers to adapt their teaching techniques, review YLs' pedagogical characteristics or needs, and subsequently rearrange the classroom environment.…”
Section: Challenges Of Teylmentioning
confidence: 99%